Evaluation of invasive tumour front in primary and secondary oral squamous cell carcinoma – A reliable prognostic parameter - Hemal Joshi; Neelampari Parikh; C Nandini; Garima Bhatt; Sandeep Jain; Ashwini Parmar (Advances in Human Biology, 2023)
Introduction: Oral squamous cell carcinoma (OSCC) is the most common malignant epithelial neoplasm affecting the oral cavity. Recent work indicates that morphological and molecular characteristics of tumour cells at invasive tumor fronts (ITF) underlie the biological aggressiveness of OSCC. The aim of the study was to compare the pattern of invasion (POI) (Type I to V) at tumour–host interface in 150 primary and 50 secondary OSCC cases. Materials and Methods: Both pre-dominant POI and worst POI was evaluated in all cases. Pre-dominant pattern of invasion and worst pattern of invasion (WPOI) were compared with Broder's grading system. Statistical analysis was done using a statistical software package (SPSS) and Fisher's exact test. Results: Results showed that the WPOI pattern also moves towards higher scores as the grade increases. Conclusion: We thus conclude that POI could serve as an individual prognostic marker irrespective of the histologic differentiation of the tumour.